Ultrastructural study of the coagulating gland of Wistar rats submitted to experimental chronic alcohol ingestion - Cagnon, V. H. A.; Garcia, P. J. [UNESP]; Martinez, F. E. [UNESP]; Martinez, M. [UNESP]; Padovani, C. R. [UNESP] (Wiley, 1996)
Morphological changes of coagulating gland of Wistar rats submitted to the experimental chronic alcoholism were noted. Ultrastructurally, it was observed reduction of the granular endoplasmic reticulum cisternae and nuclei with basal position and irregular shape. The epithelial cells presented pycnotic nuclei and the mitochondrial cristae disappeared, characteristic of cellular degeneration.
Keywords: accessory sexual glands; alcohol; coagulating gland; ultrastructural; accessory sex gland; alcoholism; animal cell; animal model; animal tissue; cell degeneration; cell ultrastructure; electron microscopy; endoplasmic reticulum; epithelium cell; histopathology; male; mitochondrial membrane; nonhuman; priority journal; prostate; rat; Animals; Cell Nucleus; Endoplasmic Reticulum, Rough; Epithelial Cells; Epithelium; Ethanol; Genitalia, Male; Male; Microscopy, Electron; Mitochondria; Rats; Rats, Wistar